Discovery of the new Coptotriche species in China revealed two novel host-plant families and host-plant orders for Tischeriidae, a family of stenophagous, leaf-mining lepidopterans - Xu, Jiasheng; Dai, Xiaohua; Rimšaitė, Jolanta; Diškus, Arūnas; Stonis, Jonas R. (Zootaxa, 2021)
The article describes three new species of Coptotriche Walsingham, 1890 from China and adjacent northern Vietnam: C. camptotheca Xu & Dai, sp. nov. feeding on Camptotheca acuminata Decne. (Nyssaceae); C. turpinia Xu & Dai, sp. nov. feeding on Turpinia arguta (Lindl.) Seem. (Staphyleaceae); and C. asiana Diškus & Stonis, sp. nov. The latter appeared to be a narrow oligophagous species feeding on various Symplocos Jacq.: S. sumuntia Buch.-Ham. ex D. Don, S. poilanei Guill., and Symplocos glauca (Thunb.) Koidz. (Symplocaceae). Nyssaceae and Staphyleaceae are novel host-plant families of Tischeriidae. The new species are illustrated with photographs of adults, male and female genitalia, and leaf mines. The article also briefly discusses about the proportion of monophagous and oligophagous species of Tischeriidae.